Hearing Loss and Disorders: The Repercussions of Climate Change - Sherratt, Sue (American Journal of Audiology, 2023)
Climate change is considered to be the greatest threat to human health in the 21st century, and its effects are accelerating. Extensive research has clearly demonstrated its increasing impact across the continuum of health conditions. Despite this, there has been limited attention to the ramifications of climate change on hearing loss and hearing disorders. This lack of consideration is somewhat surprising as the environment itself and its changing nature have a substantial effect on hearing.Tackling climate change could be the greatest global health opportunity of the 21st century. To address this issue, this tutorial provides a general introduction to climate change and its three major elements (pollution, infectious diseases, and extreme weather events) and their effects on health. The substantial consequences of climate change for the incidence, development, and exacerbation of hearing loss and disorders are clearly described and detailed.The challenge of responding to this very real and escalating threat to hearing requires a combination of prevention, advocacy, and education. These three roles place audiologists in the perfect position to take action on the far-reaching effects of climate change on hearing loss and disorders. To respond to this challenge and to fulfill these roles, several strategies, ranging from the individual level to the global level, are delineated for audiologists to incorporate into their practice.
openalex: W4387446041
Keywords: _z:class:countries; openalex:import; openalex:yes